2012
DOI: 10.1016/j.neuropharm.2012.07.031
|View full text |Cite
|
Sign up to set email alerts
|

7-Nitroindazole down-regulates dopamine/DARPP-32 signaling in neostriatal neurons in a rat model of Parkinson's disease

Abstract: a b s t r a c tNeuronal nitric oxide synthase (nNOS) is involved in the regulation of diverse intracellular messenger systems in the brain. Nitric Oxide (NO) contributes to inducing signaling cascades that involve a complex pattern of phosphorylation of DARPP-32 (in Thr-34), which controls the phosphoproteins involved in neuronal activation. However, the role of NO in the pathophysiology of Parkinson's disease (PD) and its effect in striatal neurons have been scarcely explored. In the present work, we investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 61 publications
4
24
0
Order By: Relevance
“…These alterations in the proteome might be expected when considering that as destruction of afferent SNc dopamine neurons proceeds, there is a concomitant loss of proteins related to dopaminergic connectivity (i.e., synapses) within the striatum. Such findings support previous assertions that nigro-striatal denervation negatively affects DARPP-32 expression [24], though this contrasts with other (indirect) estimations suggesting that denervation may not affect striatal DARPP-32 levels [25]. It will be important to clarify the effect of dopamine denervation on DARPP-32 expression in the striatum of human PD sufferers, as inactivation of DARPP-32 in mice can significantly reduce the possibility of l-dopa induced dyskinesias [26].…”
Section: Discussionsupporting
confidence: 92%
“…These alterations in the proteome might be expected when considering that as destruction of afferent SNc dopamine neurons proceeds, there is a concomitant loss of proteins related to dopaminergic connectivity (i.e., synapses) within the striatum. Such findings support previous assertions that nigro-striatal denervation negatively affects DARPP-32 expression [24], though this contrasts with other (indirect) estimations suggesting that denervation may not affect striatal DARPP-32 levels [25]. It will be important to clarify the effect of dopamine denervation on DARPP-32 expression in the striatum of human PD sufferers, as inactivation of DARPP-32 in mice can significantly reduce the possibility of l-dopa induced dyskinesias [26].…”
Section: Discussionsupporting
confidence: 92%
“…These mismatches have also been reported in the dorsal and central nuclei of ventral telencephalon of zebrafish [Robra and Thirumalai, 2016], in the lateroventral septum, cerebellum and reticular formation of amphibians , the septal region, the superficial part of the medial cortex, pretectum and rhombencephalic ventromedial tegmentum of reptiles [Smeets et al, 2001[Smeets et al, , 2003, and in the neocortex and cerebellum of mammals [Ouimet et al, 1984[Ouimet et al, , 1992. These data support that DARPP-32 may not only be regulated by dopamine, but also by glutamate, serotonin, noradrenalin, nitric oxide, or somatostatin Svenningsson et al, 2002;Andersson et al, 2005;Nishi et al, 2005;Hara et al, 2010;Rajput et al, 2012;Yuste et al, 2012].…”
Section: Rhombencephalon and Upper Spinal Cordsupporting
confidence: 79%
“…It suggests that without affecting the expression of DARPP32 (Fig. 6), AMI potentiated the dopamine signaling pathway by increasing the activation of DARPP32 (45,46). We also found that the marker of de novo neuron synthesis, doublecortin (DCX), was significantly elevated by AMI (Fig.…”
Section: Volume 290 • Number 5 • January 30 2015mentioning
confidence: 70%